The Portrait Of Good Governance Implementation Onto Padang City Government In The Development Of Sustainable Tourism - Eka SISKAWATI; Zahara ZAHARA; Haniva Dela GUSTA (Journal of Tourism Economics and Policy, 2021)
This article describes on how the implementation of good governance is carried out by Padang City Government in sustainable tourism management. This research is aimed to (1) Overseeing the good governance implementation in Padang City Government in term of the development of sustainable tourism destinations. (2) Analyzing the sustainable tourism management viewing it from agency theory by using three approaches of agency relationship; the relationship between executive and legislative; the relationship between legislative and public; and the relationship in budgeting context. It is a qualitative descriptive research, and performed in Padang City Culture and Tourism Office. More over, data collection utilizes observation, interview, and documentation. The good governance principle employed in this research are accountability, participation, and transparency. The result shows that the implementation of good governance at Padang City Culture and Tourism Office has been achieved well. It is as a result of the agency relationships occured within local government; the relationship with the executive in the role of Culture and Tourism Office, with the legislative in the role of Padang City Mayor, and with public as the community.